Duodenal lipoma associated with ectopic duodenal glands - Cao, Dianbo (PAGEPress Publications, 2011)
Duodenal lipomas are relatively uncommon and are rarely responsible for clinical symptoms. Occasionally, searching for aetiology of gastrointestinal bleeding leads to the final diagnosis of duodenal lipomas. Here, we present the case of a 68-year-old woman who suffered with repeated melena and weight loss. Endoscopy, abdominal computed tomography (CT) and histopathological outcomes are described in this case of duodenal lipoma with ectopic duodenal glands.